ANALISIS KOMPARASI MODEL PREDIKSI FINANCIAL DISTRESS ALTMAN, SPRINGATE, GROVER DAN OHLSON PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - Hastuti, Rini Tri (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2015)
This study purpose to determine the most accurate bankruptcy prediction model in order to suitable for use in its application to manufacturing companies in Indonesia, and to determine whether there is a difference Altman models with Springate models, Altman models with Grover models, and Altman models with Ohlson models. Scope of the study is limited to manufacturing industry companies listed on the Indonesia Stock Exchange during the years 2011-2013. This study comparing four bankruptcy prediction model by using statistic descriptive analysis techniques also Kolmogorov-Smirnov normality test and paired test analysis techniques sample t-test with the help of SPSS program. Conclusion of this study showed significant differences between the models Altman with Springate models, Altman models with Grover models, and Altman models with Ohlson models. And the highest level of accuracy achieved by the Grover models.